Kinetic Monte Carlo study of atomic diffusion in the FeAl intermetallic compound - Manrique Castillo, E. (2011)
The atomic diffusion in the FeAl intermetallic compound with B2 ordered structure were studied by the kinetic Monte Carlo method. We use the pair interactions up to second neighbors with periodic boundary conditions to avoid surface effects. Diffusion constants was determined as a function of temperature, covering both ordered and disordered phases. In addition, we calculate the autocorrelation function which shows first, highly correlated jumps of the vacancy in the lattice at low temperatures and second, the atoms that jump to positions of its own sublattice at moderate temperatures.